Gevorg Ghukasyan, The Armenian Lobby of Europe: TheEssence and Context of Ethnic Lobbying - Petrosyan, Gegham (YSU Journal of International Affairs, 2024)
The purpose of the work is to highlight the transnational political role of ethnic lobbying in modern political processes, assess the structural-operational possibilities of the European Armenian lobby, the characteristics of its activities, identify lobbying entities and understand the scope of their influence and the possibility of role in RA-EU relations. The role of the institution of ethnic lobbying in the process of political modernization was evaluated. At the same time, the possibilities of ethnic lobbying to act as an operator of "soft power" were considered, the possibilities of lobbying in the conditions of the value system of multiculturalism were revealed, the chain of interaction and interaction of the "homeland-diaspora-host state" triangle was systematically characterized. The lobbying structures of the Armenian diaspora in Europe and the main directions and tools of their activities were identified, and the political behavior of the EU regarding the Karabakh problem was revealed. The intra-European perception of ethnic lobbying, the institutional and legislative possibilities of lobbying and its variety of ethnic lobbying in the EU have been analyzed. The monograph is intended for political scientists, historians, Armenologists, the governing body, professors and students of RA higher educational institutions, as well as the general reading public.